Waqf Property Management Through the Maqasid Al-Shariah Approach - FISOL, WAN NAZJMI MOHAMED; BAKAR, MARINA ABU; AHMAD, AKLI (The journal of contemporary issues in business and government, 2021)
Waqf is an important instrument in a country’s economic system as it ensures that the socio-economic development can be achieved more effectively. However, there are several issues that hinder the management and development process of waqf land for the purpose of socio- economic development of ummah. These happened because of the existence of several conditions set by the donor (waqif) of waqf properties. Therefore, this study is conducted to identify the views of Shariah scnorholars from the aspect of changing the conditions of waqf made by the donor (waqif) through the approach of Maqasid Shariah namely “Tasarruful Imami ‘Ala al- Ra'iyyati Manuthun bi al-Maṣlaḥah”. In Malaysia, State Islamic Religious Council (SIRC) is responsible in managing and administering the development of waqf properties in each state. In order to achieve a holistic devolopment, it is vital to look at the broader maslahah (benefits) and needs involved in waqf properties. This study applies qualitative method and the data collection involves library research approach using references from Islamic jurisprudence classical books. The data is analysed using content analysis method. The results of the study found that method of changing the use of waqf property towards a more beneficial purpose is more accurate with the definition and principle of maqasid al-Shariah in obtaining the benefit and avoiding the harm (jalb al-Manfa‘ah wa daf‘ al-Madarrah). The findings are beneficial in helping the management and development of waqf properties and the socio-economic of society in Malaysia as a whole.